Assessment of Microbial Load in Made Tea and Antimicrobial Property of Made Tea Infusion. - Md Monir Hossain,; Rezaul Karim,; Shamima Begum,; GM Rabiul Islam,; Md Mozammel Hoque, (Universiti Kebangsaan Malaysia, 2013)
This study aimed to find out that a cup of tea is or is not safe for human health from microbial contamination and to point out the antimicrobial property of made tea liquor.